Enclaves of activism and taste: Consumer cooperatives in Poland as alternative food networks - Bilewicz, Aleksandra; Spiewak, Ruta (Socio.hu Társadalomtudományi Szemle, 2015)
Alternative Food Network (AFN) is a broad term encompassing many initiatives connected by the aim to build an alternative to globalized industrial food production and distribution. AFN is a term that covers many ways of connecting producers and consumers on the local level, e.g. community supported agriculture (CSA), farmer markets or food cooperatives. In this article, the authors analyse the newly established consumer cooperatives all over Poland, as a local form of alternative food network. The authors describe the specific character of this type of AFN, both from the consumers’ and producers’ point of view, and reflect on the issue of how specific social and historical background influence their development. The authors also discuss the “enclave” character of the cooperatives, that is suggested to be specific to the Polish type of AFN. The cooperatives studied varied considerably, so the authors propose two distinct types: activist and consumeroriented. Polish food cooperatives possess characteristics that the authors have decided to label with a common term of “enclave” character. Keywords: models of alternative food networks, consumer cooperatives, sustainable farming, social enclaves.